Peranan Information Overload terhadap Konsentrasi pada Proses Belajar Daring Peserta Didik di SMAN 1 Kotabaru - Mutiara Hikmah; Rusdi Rusli; Marina Dwi Mayangsari (Provitae: Jurnal Psikologi Pendidikan, 2022)
The COVID-19 pandemic brings new challenges to the teaching and learning process through online learning. Online learning that is carried out efficiently will have positive effects. In fact, online learning in Indonesia does not run efficiently and has various impacts on several aspects, one of which is concentration. Online learning activities require high concentration and a supportive environment. Inefficient online learning results in an excess of information from the environment, thus affecting the level of concentration of students during learning activities. This fact underlines the purpose of this study, namely to investigate the role of information overload on concentration during the online learning process in students of SMAN (Public Senior High School) 1 Kotabaru. This study is quantitative research using the information overload adaptation scale and concentration scale. The sampling was carried out using the cluster random sampling technique. The subjects were students of SMAN 1 Kotabaru as many as 249 students. Data were analyzed using the simple linear regression with the results showing that the information overload had a significant negative role in predicting concentration. It means that the higher the individual experienced information overload, the lower the concentration the individual had. Meanwhile, the information overload was not the only factor that affected concentration. There were other factors affecting concentration but were not investigated in this study.